Medical Treatment of Intoxications and Decontamination of Chemical Agent in the Area of Terrorist Attack - Dishovsky, Christophor; Pivovarov, Alexander; Benschop, Hendrik; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2006)
The use of sarin in the terrorist acts in Matsumoto city and Tokyo underground was considered by a number of specialists as a new era in terrorism. In addition to chemical weapons, terrorists can use a great variety of toxic chemicals from chemical industry, agriculture or products released from terrorist acts on industrial facilities. Evidently, the arsenal of chemical agents that can be used as terrorist agents is practically unlimited. The risk of exposure to chemical agents which could be used in terrorist acts is real. Therefore, the readiness for defense in a case of chemical terrorism should be enhanced. Decontamination and medical treatment are important aspects of protection from effects after intoxications with chemical agents. The main aspects of the book are: - New approaches in pre-treatment and prophylaxis of nerve agent intoxication - Diagnosis of exposure to chemical agents - Therapy of chemical agent intoxication - Development of personal decontamination
CURRENT PROBLEMS OF CHEMICAL TERRORISM -- PROBLEMS OF CHEMICAL TERRORISM AND WAYS OF ITS OVERCOMING -- TOXIC CHEMICALS AND RADIOACTIVE SUBSTANCES AS REASON OF OCCURRENCE OF ACUTE POISONING IN UKRAINE -- BIOMONITORING OF EXPOSURE TO CHEMICAL WARFARE AGENTS -- NON-RULED MARKET ECONOMY AS A SOURCE OF CHEMICAL TERRORISM. AUTOMOTIVE FUEL: QUALITY AND ENVIRONMENTAL SAFETY -- ROLE OF THE CHEMICAL WEAPONS CONVENTION IN COMBATING CHEMICAL TERRORISM -- CHEMICAL INCIDENT SIMULATOR: A NEW APPROACH FOR DERIVING PASSIVE DEFENCE REQUIREMENTS -- OPCW CONCEPT OF ASSISTANCE UNDER ARTICLE X -- ENVIRONMENTALLY HAZARDOUS PROJECTS IN UKRAINE AS ATTRACTIVE TARGETS FOR TERRORIST ACTS -- DIOXINES: THREAT OF MISUSE IN POSSIBLE ACTS OF CHEMICAL TERRORISM -- DIAGNOSIS OF EXPOSURE TO CHEMICAL AGENTS AND MEDICAL TREATMENT OF CHEMICAL AGENT INTOXICATION -- EPIDEMIOLOGY OF CHEMICAL CRISIS, PUBLIC HEALTH IMPACT, SPECIFIC MEDICAL COUNTERMEASURES AND EDUCATION -- MODERN APPROACHES TO MEDICAL TREATMENT OF POISONING CAUSED BY NEUROPARALITIC ANTICHOLINESTERASE COMPOUNDS -- CERTAIN PROBLEMS OF RENDERING MEDICAL ASSISTANCE UNDER ACTS OF CHEMICAL TERRORISM -- EFFICACY OF PRETREATMENT AND TREATMENT AGAINST SOMAN INTOXICATION -- BIOMEDICAL SAMPLING FOLLOWING A CHEMICAL WARFARE AGENT TERRORIST EVENT - AN OPCW PERSPECTIVE -- PARTICULARITIES IN RESEARCH, PRODUCTION AND ACQUISITION OF THE PHARMACEUTICAL PRODUCTS FOR NBC MEDICAL PROTECTION -- TOXICOKINETICS IN HELPING OF DIAGNOSES AND TREATMENT OF CHEMICAL POISONING -- DEVELOPMENT OF PERSONAL DECONTAMINATION IN CASE OF INTOXICATION WITH CHEMICAL AGENT -- ASPECTS OF DECONTAMINATION IN CASE OF RELEASE OF TOXIC SUBSTANCES OR USE OF CHEMICAL WARFARE AGENTS -- PERSONAL DECONTAMINATION IN CASES OF CHEMICAL TERRORIST ATTACKS -- HARMFUL CHEMICAL-INDUSTRY INCIDENTS EFFECTS PROGNOSIS SYSTEM OF THE TERRITORIAL CENTER FOR EMERGENCY MEDICINE: SUPPLY OF INFORMATION AND ANALYSIS DATA -- PURIFICATION OF DRINKING WATER FROM 134, 137Cs, 89,90Sr, 60Co AND 129I -- RESEARCH OF DECONTAMINATION EFFICIENCY OF CONTAMINATED CAMOUFLAGE CLOTHING WITH APPLIED METHODS AND MEANS IN REPUBLIC OF BULGARIA -- ALLEVIATION OF TOXIC IMPACT OF CHEMICAL AGENTS ON HUMAN ORGANISM -- USING OF COLD PLASMA FOR PURIFICATION OF PERIOD CHEMICALLY POLLUTED WATER IN EXTREME -- THE ROLE OF CLINICAL TOXICOLOGY IN MINIMIZING ADVERSE HEALTH EFFECTS RELATED TO CHEMICAL DISASTERS -- PREVENTION OF GAS SEEPING INTO BUILDINGS THROUGH CONSTRUCTIVE MATERIALS -- BIOLOGICAL METHOD FOR THE WATER, FOOD, FODDERS AND ENVIRONMENT TOXIC CHEMICAL MATERIALS CONTAMINATION INDICATION.
Keywords: MEDICINE; TOXICOLOGY; CHEMICALS -- SAFETY MEASURES; EMERGENCY MEDICINE; CRITICAL CARE MEDICINE; MEDICINE, INDUSTRIAL; BIOMEDICINE; PHARMACOLOGY/TOXICOLOGY.; EMERGENCY MEDICINE; OCCUPATIONAL MEDICINE/INDUSTRIAL MEDICINE; INTENSIVE / CRITICAL CARE MEDICINE; SAFETY IN CHEMISTRY, DANGEROUS GOODS